Evolving and augmenting worth mapping for family archives - Cockton, Gilbert; Sellen, Abigail; Banks, Richard; Kirk, Dave (Proceedings of British HCI 2009, 2009)
We describe the process and outcomes of developing worth maps from field research and initial design sketches for a digital Family Archive. Worth maps have evolved from Hierarchical Value Models (HVMs) in consumer psychology, which were developed to support marketing and advertising activities. Use of worth maps in the Family Archive context resulted in a form that was much simpler and more flexible than both HVMs and their initial adaptation for HCI use. The evolution of worth maps from HVMs has repositioned a ‘late’ technique from marketing and advertising, used around release to manufacturing, to an early approach for the ‘fuzzy front end’ of design. This evolution was guided by a need to support designing as connecting by forming explicit associations between design elements and human values. We describe the evolution and outcomes of a worth mapping approach across two months of usage within a multidisciplinary research setting. Two supporting worth centred design resources were developed: one to organize field materials (a worth board) and another to simplify worth map structure (user experience frames). During this process, we identified and refined a range of design elements and relevant human values for initial conceptual exploration of an innovative table top computer application. We end with an evaluation of the process and outcomes, complemented with insights from subsequent applications of worth maps. The resulting worth maps and associated resources were (and remain) valuable, but experiences during this and other uses indicated that further improvements are needed.